2018
DOI: 10.1016/j.stemcr.2018.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Extracellular Signal-Regulated Kinase 5 Pathway to Suppress Human Chronic Myeloid Leukemia Stem Cells

Abstract: SummaryTyrosine kinase inhibitors (TKi) are effective against chronic myeloid leukemia (CML), but their inefficacy on leukemia stem cells (LSCs) may lead to relapse. To identify new druggable targets alternative to BCR/ABL, we investigated the role of the MEK5/ERK5 pathway in LSC maintenance in low oxygen, a feature of bone marrow stem cell niches. We found that MEK5/ERK5 pathway inhibition reduced the growth of CML patient-derived cells and cell lines in vitro and the number of leukemic cells in vivo. Treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 66 publications
(124 reference statements)
3
25
0
Order By: Relevance
“…3a). CD26 was expressed at high levels in KCL22, but not in K562 and LAMA-84 cells, as previously reported by us and others [13,62] (Fig. 3a).…”
Section: Effects Of Imatinib and Ponatinib On Stem Cell Markers In CMsupporting
confidence: 87%
See 3 more Smart Citations
“…3a). CD26 was expressed at high levels in KCL22, but not in K562 and LAMA-84 cells, as previously reported by us and others [13,62] (Fig. 3a).…”
Section: Effects Of Imatinib and Ponatinib On Stem Cell Markers In CMsupporting
confidence: 87%
“…This conclusion is further supported by the finding that the progressive fading off of TKi effect was paralleled by the consistent effectiveness of XMD8-92, which we previously showed to exhibit an enhanced inhibitory action on the relatively more immature CML cells and on the maintenance of the CML stem cell compartment. Besides providing interesting pieces of evidence with respect to the effect of imatinib versus ponatinib, our experiments indicated that serial CFA assays are adequate to test the effects of drugs on leukemia progenitor/stem cell subsets [8,9,12,13,38,73].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Furthermore, knockout of ERK5 in keratinocytes prevents inflammation-driven tumorigenesis [30]. Knockdown of ERK5 (or MEK5) by siRNA has also shown the therapeutic potential of the ERK5 pathway in mutant BRAF-driven melanoma [31,32,33], mutant KRAS-driven pancreatic ductal adenocarcinoma (PDAC) [34], as well as prostate [35], breast [36] and bladder cancers [37]. There are conflicting results obtained with ERK5 siRNA in hepatocellular carcinoma (HCC) [38,39].…”
Section: The Erk5 Signalling Pathway In Health and Diseasementioning
confidence: 99%